Effect of Tele-Nutrition Counselling and Physical Activity on Nutrition Knowledge, Attitudes and Practices in Obese Adults - Prasetyo, Teguh Jati; Pramesti , Aqilah Arum; Ramadhan, Gumintang Ratna; Surijati, Katri Andini; Listiandi, Arfin Deri; Sulistyaning, Afina Rachma; Khoiriani, Izzati Nur; Wicaksari, Sifa Aulia (YCAB Publisher, 2025)
Background: Obesity is a condition of excessive body weight. Tele-nutrition counselling is a remote nutrition service as an effort to treat obesity. Physical activity can overcome obesity conditions due to the process of burning calories which causes weight loss. Objectives : The purpose of this study was to determine the effect of tele-nutrition counselling and physical activity on knowledge, attitudes, nutrition practices (KAP) in obese adults. Methods: This study used Quasy experimental with pre-post-test control group design. There was 56 obese adult respondents were divided into 2 groups that were given physical activity intervention, moreover the experimental group was given tele-nutrition counselling intervention. KAP scores were taken using a valid and reliable questionnaire. The intervention was conducted online. Data analysis used Wilcoxon and Independent t-test. Results: There was an effect of the intervention on knowledge (p=0.009), attitude (p=0.021), nutrition practices (p=0.000) of the experimental group. There was no effect on knowledge (p=0.477), attitude (p=0.935), but there was an effect on nutrition practices (p=0.003) in the control group. There was a difference in knowledge (p=0.023) but no difference in attitude (p=0.116) and nutrition practices (p=0.213) between the two groups. Conclusion: There was an effect of the intervention on nutrition practices in both groups. There was an effect of the intervention on knowledge, nutritional attitudes in the experimental group but not in the control group. There is a difference in the effect of the intervention on knowledge but there is no difference in the effect on attitudes and nutrition practices between the two groups. Keywords: adults; nutrition knowledge; obese; physical activity; tele-nutrition counselling